Relationship between Knowledge and Attitude towards Motivation of Postpartum Mothers to Undergo Breast Care at PMB Sulami Eromoko - Amita, Migita Vidia; Enyk Yunanto (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2025)
Breast care for postpartum mothers can prevent various problems such as mastitis, blocked milk ducts, and breast infections. Healthy breasts support smooth breastfeeding which also affects the well-being of the baby. The motivation of postpartum mothers to carry out breast care is influenced by the knowledge they have and their attitudes towards breast care itself. Good knowledge will encourage a positive attitude, which then increases the motivation to take actions that are beneficial for breast health. The purpose of thstudy was to determine the relationship between knowledge and attitudes of postpartum mothers and the motivation of postpartum mothers to carry out breast care. The design of this study was a cross-sectional approach. The population of postpartum mothers who gave birth in December 2024 to February 2025 at independent midwifery clinic Sulami. The sampling technique used total sampling and the data was analysed using chi square. The respondents in this study were 25 postpartum mothers with the majority of postpartum mothers in the non-risk age category (80%), 60% had high school education, and 15 postpartum mothers did not work (housewife). The knowledge of postpartum mothers is in the good category (40%) and the attitude of postpartum mothers is in the positive category (76%), while the motivation of postpartum mothers in carrying out breast care is included in the good category (52%). The results of the study showed that the knowledge and motivation of postpartum mothers ρ = 0.01, which means that the knowledge of postpartum mothers is related to the motivation of postpartum mothers in carrying out breast care. Meanwhile, the attitude and motivation of postpartum mothers ρ = 0.03, which means that the attitude of postpartum mothers is related to the motivation of postpartum mothers in carrying out breast care.